1984
DOI: 10.1007/bf00177902
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in human brain tumors

Abstract: Polyamine levels have been studied in brain tumor patients. We focused our study on the relationship between tumor, cerebrospinal fluid (CSF) and red blood cell (RBC) polyamine levels. Our results are the following: Polyamine levels in CSF are consistently increased, whatever the histological type may be. The highest tumoral concentrations are found in medulloblastoma. In glioblastomas, the RBC spermidine levels are higher than in the other types of tumors and there is a highly significant correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…The results obtained through our newly developed method are summarized in Table 2. Levels of Spm, Spd, and Cad and Put in human erythrocytes from healthy subjects were within the range reported as normal in previous publications [37,[39][40][41]. As shown in Table 2, the values of Spm and Spd which significantly increased in the patient with vesical cancer were consistent with the known facts that erythrocyte Spm and Spd levels are elevated and can serve as an index for tumor progression [22].…”
Section: Analysis Of Erythrocytessupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained through our newly developed method are summarized in Table 2. Levels of Spm, Spd, and Cad and Put in human erythrocytes from healthy subjects were within the range reported as normal in previous publications [37,[39][40][41]. As shown in Table 2, the values of Spm and Spd which significantly increased in the patient with vesical cancer were consistent with the known facts that erythrocyte Spm and Spd levels are elevated and can serve as an index for tumor progression [22].…”
Section: Analysis Of Erythrocytessupporting
confidence: 91%
“…Therefore, the present method was used to quantify polyamines in human erythrocytes. Polyamine levels were expressed in nmol per 8610 9 erythrocytes [39][40][41]. A representative electropherogram of the samples separation is shown in Fig.…”
Section: Analysis Of Erythrocytesmentioning
confidence: 99%
“…They are applied to biological fluids including urine [9 -17], serum [9,12,13], seminal liquid [18], cerebrospinal fluid [11, 19 -21], bile [22], colostrum [23], saliva [24], erythrocytes [20,25,26], and plasma [9,25,27]. Since most biogenic amines cannot be detected directly with considerable sensitivity, chemical derivatization is usually performed.…”
Section: Introductionmentioning
confidence: 99%
“…Cohen [8] had shown that free polyamines were transported mainly in red blood cells (RBC) and Tadolini [9] confirmed their intracellular location. Moulinoux [10,11] found elevated levels of RBC polyamine in patients with lung and liver malignancies and in 1984 studied free spermine and spermidine levels in the RBC of patients with intracranial turnouts [12]. The possibility that RBC polyamine levels give some indication of intracranial tumour activity is an attractive concept in view of the difficulties and dangers of obtaining CSF for routine marker analysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…RBC polyamine levels were investigated in a number of patients with a variety of intracranial tumours using the technique of Moulinoux [12]. The levels of circulating free spermine and spermidine were measured before and after operation to investigate whether 1.…”
Section: Introductionmentioning
confidence: 99%